Participatory Action Plans for Functional Level Strategies Based on SPEED Model of Madan Processing Community Enterprise Operator - Sangkhamart, Khatawut (Ph.D. in Social Sciences Journal, 2023)
This research article aims to formulate a participatory action plan for Madan processing community enterprise entrepreneurs. According to the participatory action research process and to explore the results of the success dimensions of the Participatory Action Plan of Madan Processing Community Enterprise Entrepreneurs. The research is mixed method research between qualitative research and survey research. The population in the research are Entrepreneurs in Madan Processing Community Enterprise totaling 63 people in Nakhon Nayok Province using interview and questionnaire forms for data analysis with content analysis and descriptive statistical analysis. The results of the research reveal that: concluded that Participatory Action Plan According to the SPEED Model, an action plan will be established consisting of (1) A Live action plan for selling products (2) Writing product stories through online media (3) OTOP product standard training (4) Organizing flea market activities community products “Mueang Madan” and (5) brand design/new packaging. In the success dimension section of the action plan. The cultural dimension is that people in the community have a culture or an economical way of life. Savings have an average value of 4.24 with an SD of 0.96. The psychological dimension is that people in the community feel proud in bringing local objects to their benefit. The mean was 4.17 with an SD of 0.90. The social dimension is that people in the community are kind. The mean value of caring for each other was 4.14 with an SD of 0.90 and the economic dimension was that the community had more income from selling products during the activity according to the action plan. The mean was 4.07 with a SD of 0.79.